Maturation of molybdoenzymes and its influence on the pathogenesis of non-typeable Haemophilus influenzae - Dhouib, Rabeb; Pg Othman, Dk S. M.; Essilfie, Ama-Tawiah; Hansbro, Phil M.; Hanson, Jeffrey O.; McEwan, Alastair G.; Kappler, Ulrike (Frontiers in Microbiology, 2015)
Mononuclear molybdenum enzymes of the dimethylsulfoxide (DMSO) reductase family occur exclusively in prokaryotes, and a loss of some these enzymes has been linked to a loss of bacterial virulence in several cases. The MobA protein catalyzes the final step in the synthesis of the molybdenum guanine dinucleotide (MGD) cofactor that is exclusive to enzymes of the DMSO reductase family. MobA has been proposed as a potential target for control of virulence since its inhibition would affect the activities of all molybdoenzymes dependent upon MGD. Here, we have studied the phenotype of a mobA mutant of the host-adapted human pathogen Haemophilus influenzae. H. influenzae causes and contributes to a variety of acute and chronic diseases of the respiratory tract., and several enzymes of the DMSO reductase family are conserved and highly expressed in this bacterium. The mobA mutation caused a significant decrease in the activities of all Mo-enzymes present, and also resulted in a small defect in anaerobic growth. However, we did not detect a defect in in vitro biofilm formation nor in invasion and adherence to human epithelial cells in tissue culture compared to the wild-type. In a murine in vivo model, the mobA mutant showed only a mild attenuation compared to the wild-type. In summary, our data show that MobA is essential for the activities of molybdenum enzymes, but does not appear to affect the fitness of H. influenzae. These results suggest that MobA is unlikely to be a useful target for antimicrobials, at least for the purpose of treating H. influenzae infections.